Distance between parapatellar portal and intra-articular space for needle positioning in knee osteoarthritis (Medical Journal of Indonesia, 2013)
Background: Intra-articular injection is a common therapeutic procedure in osteoarthritis (OA) that need high accuracy. This study was aimed to measure the distance between parapatellar skin and intra-articular space as a guidance to choose the length of needle needed to perform intra-articular injection. Methods: Twenty one knees MRI were taken from 16 females with knee osteoarthritis. The length of the needle needed to reach intra-articular space was reconstructed by drawing straight line from skin to intra-articular fluid. Paired t-test was using to analyze the mean difference of measurement of left side compare with right side with significant indicator if p-value < 0.05. Results: The entry point on both medial and lateral parapatellar were more cranial than transverse mid-patellar line. On medial portal, the closest distance from skin to intra-articular space is 27.81±7.58 mm. Mean point of entry is 4.46±2.16 mm cranial to mid-patellar line, and 14.20±4.45 mm posterior to the prominence of medial border of patella. On lateral portal, the closest distance from skin to intra-articular space is 16.84±6.79 mm. Mean point of entry is 11.10±5.94 mm cranial to mid-patellar line, and 8.91±3.83 mm posterior to the prominence of lateral border of patella. Conclusion: MRI knee osteoarthritis study showed that the mean distance between skin and intra-articular joint space of medial portal is 27.81±7.58 mm, and lateral portal is 16.84±6.79 mm. The portals on both sides is cranial to midpoint of patella, lateral appears more proximal than medial. This should be put into consideration in choosing needle length and portal projection to increase intra-articular injection accuracy.